2006
DOI: 10.1021/jp064136g
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of a Protein in the Pre Molten Globule State

Abstract: The nature of solvent molecules around proteins in native and different non-native states is crucial for understanding the protein folding problem. We have characterized two compact denatured states of glutaminyl-tRNA synthetase (GlnRS) under equilibrium conditions in the presence of a naturally occurring osmolyte, l-glutamate. The solvation dynamics of the compact denatured states and the fully unfolded state has been studied using a covalently attached probe, acrylodan, near the active site. The solvation dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
(67 reference statements)
1
28
0
Order By: Relevance
“…23 Samaddar et al studied solvation dynamics in the pre-molten globule state of GlnRS. 24 They observed that the solvation time is of the order, native > molten globule > premolten globule.…”
Section: Solvation Dynamics In Proteins and Dnamentioning
confidence: 99%
“…23 Samaddar et al studied solvation dynamics in the pre-molten globule state of GlnRS. 24 They observed that the solvation time is of the order, native > molten globule > premolten globule.…”
Section: Solvation Dynamics In Proteins and Dnamentioning
confidence: 99%
“…1,2,1719 These photophysics are strongly medium-dependent, presumably due to the molecular dipole moment increasing upon excitation and specific solvation, including hydrogen bonding. 2,19 The dyes are frequently used as probes of polarity and dynamics of the local environment in proteins 1,20,21 as well as micelles and membranes, 1,2,17,18 by measuring stationary and time-resolved fluorescence spectra. 1 The environmental dependence of Badan fluorescence lifetimes was employed, for example, in a glucose sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fundamental relationship between protein solvation and dynamics, it is important to understand the dynamical and energetic changes in the protein solvating layer that accompany the folding or unfolding process (38,39). Recent studies with fluorescent probes attached to the protein surfaces and dynamic lightscattering experiments have elucidated differences in solvation times between the fully denatured, ''premolten'' globule, molten globule, and native states (3,4). Molecular dynamics simulations have been used to point out clear differences in the secondary structure dependence of solvation dynamics between the native and a hypothetical molten globule state of the protein HP-36 (46).…”
Section: Introductionmentioning
confidence: 99%